2016
DOI: 10.1016/j.toxlet.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and nitrogen mustards induce characteristic poly(ADP-ribosyl)ation responses in HaCaT keratinocytes with distinctive cellular consequences

Abstract: Letters ; 244 (2016). -S. 56-71 https://dx.doi.org/10.1016/j.toxlet.2015In particular, we recorded substance specific as well as dose and time dependent PARylation responses using independent bioanalytical methods based on single cell immuno fluorescence microscopy and quantitative isotope dilution mass spectrometry. Furthermore, we analyzed if and how PARylation contributes to mustard induced toxicity by treating HaCaT cells with CEES, SM, and HN2 in combination with the clinically relevant PARP inhibitor AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 81 publications
(119 reference statements)
3
12
0
1
Order By: Relevance
“…Moreover, the resistant cells showed significantly higher levels of NAD + , NADH and therefore total NAD than the sensitive cells. Supporting our data, the NAD + depletion often described in the literature could also not be validated by even treatment with up to 3 mM CEES and 24 h (Mangerich et al, 2016). The NAD + decrease seems to be concentration dependent and might be achieved by increasing the SM doses adequately.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Moreover, the resistant cells showed significantly higher levels of NAD + , NADH and therefore total NAD than the sensitive cells. Supporting our data, the NAD + depletion often described in the literature could also not be validated by even treatment with up to 3 mM CEES and 24 h (Mangerich et al, 2016). The NAD + decrease seems to be concentration dependent and might be achieved by increasing the SM doses adequately.…”
Section: Discussionsupporting
confidence: 60%
“…The accumulation of glucose-6-phosphate leads to induction and secretion of proteases resulting in nuclear and cytoplasmic damage (Graham et al, 2005). The NAD + depletion often mentioned in the literature could not be validated by other studies (Mangerich et al, 2016). Otherwise, niacin, the vitamin from which NAD + and NADP + are synthesized, showed protective effects against DNA-damaging agents (Jacobson et al, 2007).…”
Section: Introductionmentioning
confidence: 75%
“…Cells were treated with 1 mM H 2 O 2 for 5 min before they were fixed in ice cold methanol for 7 min at -20°C [15]. Cover slips were washed 3 x 5 min in PBS and samples were blocked in 5% dry milk in PBS-T for 1 h at RT.…”
Section: Methodsmentioning
confidence: 99%
“…However, the moderate PARP activation induced by CEES presumably leads only to minor changes in intracellular NAD + concentrations, which speaks against the hypothesis that SM causes massive PARP activation resulting in ATP depletion, necrotic cell death, and subsequent tissue inflammation. For a detailed cell culture study characterizing the PARylation response induced by bifunctional mustards as well as a discussion of the therapeutic potential of PARP inhibitors in SM related pathologies the reader is referred to an accompanying paper (Mangerich et al, 2016) It is interesting to note that PAR formation after H 2 O 2 peaks already at 5 min post treatment (Martello et al, 2013), whereas maximum PARylation was observed 10 min post CEES treatment. One possibility for the different PARylation dynamics are substance specific toxicokinetics.…”
Section: Application Of the Optimized Cees Treatment Prototocol For Tmentioning
confidence: 99%
“…This study provides the basis for a broader characterization of sulfur and nitrogen mustard induced PARylation response and cellular consequences thereof, which is described in an accompa nying article (Mangerich et al, 2016).…”
Section: Introductionmentioning
confidence: 97%